The Study of Pharmacokinetics Parameters of Morphine Hydrochloride, Long-acting Tablets in Cancer Patients with Severe Chronic Pain Syndrome - E. A. Ezhova; I. G. Kotelnikova; A. V. Teteneva; D. V. Butuzova; K. F. Tetenev (Разработка и регистрация лекарственных средств)
Introduction. Effective drug therapy for cancer patients with chronic pain syndrome (CPS) of high intensity is one of the priorities of modern healthcare. Currently, non-narcotic and narcotic analgesics are used for pain relief according to a three-steps scheme. In the absence of contraindications, it is preferable to prescribe medications per os and prolonged forms, which will allow the patient to maintain selfcare and comfort.Aim. To study the pharmacokinetic properties of a drug with a prolonged mechanism of action «Morphine hydrochloride», in a film-coated tablet formof a dosage 30 mg, in cancer patients with severe CPS.Materials and methods. For the analysis of the pharmacokinetics of the studied drug after single and multiple doses of 20 patients who received 10-day analgesic therapy with the studied drug «Morphine hydrochloride», long-acting film-coated 30 mgtablets. manufacturer FSUE Moscow Endocrine Plant, Russia. Route of administration: per os. The study duration was 17 days: screening duration up to 7 days; duration of therapy up to 10 days.Results and discussion. The concentration of morphine in plasma was determined by HPLC-tandem mass spectrometry, within 12 hours after taking the study drug (1 of long-acting, film-coated tablet 30 mg). The following pharmacokinetic parameters were obtained on Day 5: T1/2 – 6.08 ± 4.37 hours and 14.46 ± 30.86 hours, Tmax – 2.5 ± 1.86 hours, Cmax – 43.91 ± 27.24 ng/ml. Values of pharmacokinetic parameters averaged over all days are presented. It was found that T1/2 for the studied drug T1/2 is 9.21 ± 14.94 hours, Tmax 2.87 ± 2.36 hours. The average maximum concentration (Cmax) on the day of the study drug was 36.52 ng/ml.Conclusion. As a result of the study of pharmacokinetics, it was found that the drug «Morphine hydrochloride», long-acting tablets film-coated with a of 30 mg was found in serum after oral administration after 15 minutes and reaches a maximum concentration in the blood in 3 hours, the half-life is on average 9 hours, the maximum concentration is 36.52 ng/ml.